Hubungan Perilaku Merokok Dengan Kondisi Kesehatan Fisik Pada Mahasiswa STIKes PHI Tahun 2018 - Ignatius Teguh; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2019)
Smoking a cigarette will greatly affect the increase in blood pressure, and nicotine will cause stimulation of the hormone Epinephrine (Adrenaline) which is stimulated to increase heart frequency, blood pressure, heart oxygen demand, and cause heart rhythm disorders. The purpose of this study was to examine the relationship of smoking behavior with physical health conditions in STIKes PHI students in 2018. This research is a quantitative research with analytic research using cross-sectional study design that aims to determine the relationship between smoking behavior and physical health condition of students. The results showed that most respondents' smoking behavior were filter cigarettes (98.2%), the number of consumption of 1-10 cigarettes per day (100.0%), duration of smoking ≤ 5 years (75.4%), category of light smokers (75.4%). In general, it was found that the health conditions of the respondents were in good health (86.0%). The results showed that no significant relationship was found between the independent variables (age, study program, level, regional origin and smoking behavior), with the dependent variable (health condition). It is recommended that more detailed research be conducted on respondents with different populations for comparison. Further research is also needed to see the relationship between different variables.